Inertial force assessment in cross-country sit skiers - Gastaldi, L.; Lisco, G.; Pastorelli, S. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Despite the similarity between the pushing poles gesture (PPG) in crosscountry sit skiing and double poling (DP) technique adopted by standing skiers (Holmberg et al., 2005), it is necessary to specifically focus on the gesture performed by sit-skiers. Few studies are related to adaptive cross-country skiing kinematics (Gastaldi et al., 2012).This research aims to point out a proper inertial